An In-Depth Analysis of White-Collar Crime in Dubai's Financial Sector, Legal Frameworks, and Collaborative Solutions - Komalasari, Rita; Mustafa, Cecep (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2024)
This study identifies specific legal loopholes and regulatory deficiencies contributing to white-collar crime, advocating adaptive legal reforms and a collaborative approach to fortify the legal framework. In the context of Dubai's rapidly growing economy, this study delves into the escalating global phenomenon of white-collar crime, focusing specifically on its prevalence within the emirate's financial sector. The study addresses the potential exploitation of legal frameworks and regulatory gaps, offering a contextualized analysis of the contributing factors amid Dubai's economic expansion. The research employs a comprehensive literature review to identify existing gaps in understanding, focusing on the distinctive challenges faced by Dubai. The research aims to furnish a comprehensive understanding of white-collar crime in the financial sector, emphasizing the mechanisms through which legal loopholes and regulatory shortcomings may facilitate such offenses. By pinpointing vulnerabilities, the study provides actionable insights for policymakers, regulatory authorities, and stakeholders to fortify the legal infrastructure and prevent financial misconduct. The findings not only deepen the comprehension of white-collar crime challenges in Dubai but also furnish practical insights for mitigating future risks, presenting a roadmap for policymakers to combat the evolving nature of financial offenses in the region. In conclusion, this study underscores the urgent need for adaptive legal reforms and enhanced regulatory measures to address the vulnerabilities within Dubai's financial sector.